1997
DOI: 10.1074/jbc.272.36.22417
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Sulfinate Desulfinase, a NIFS-like Protein ofEscherichia coli with Selenocysteine Lyase and Cysteine Desulfurase Activities

Abstract: Selenocysteine lyase (EC 4.4.1.16) exclusively decomposes selenocysteine to alanine and elemental selenium, whereas cysteine desulfurase (NIFS protein) of Azotobacter vinelandii acts indiscriminately on both cysteine and selenocysteine to produce elemental sulfur and selenium respectively, and alanine. These proteins exhibit some sequence homology. The Escherichia coli genome contains three genes with sequence homology to nifS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
155
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 59 publications
(34 reference statements)
2
155
0
Order By: Relevance
“…CsdB shows significant selectivity for selenocysteine, and the recently reported crystal structure (36) reveals fundamental differences in structure compared with that predicted for IscS. Cysteine-sulfinate desulfinase and CsdB (SufS) have been grouped separately from IscS based on amino acid sequence homology (33). We have found no obvious phenotype for deletion of cysteine-sulfinate desulfinase or csdB, 3 although it has been reported that sufS mutants cannot utilize ferrioxamine B as an iron source (35).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…CsdB shows significant selectivity for selenocysteine, and the recently reported crystal structure (36) reveals fundamental differences in structure compared with that predicted for IscS. Cysteine-sulfinate desulfinase and CsdB (SufS) have been grouped separately from IscS based on amino acid sequence homology (33). We have found no obvious phenotype for deletion of cysteine-sulfinate desulfinase or csdB, 3 although it has been reported that sufS mutants cannot utilize ferrioxamine B as an iron source (35).…”
Section: Discussionmentioning
confidence: 77%
“…coli contains three genes with homology to nifS. In addition to iscS, these are cysteine-sulfinate desulfinase (33) and csdB (34). The csdB gene is identical to sufS, which was found to be required for the stable maintenance of the [2Fe-2S]-containing Fhuf protein in E. coli (35).…”
Section: Discussionmentioning
confidence: 99%
“…The highest Z scores were calculated to be 62.4 for human SCL (an as yet unpublished structure, PDB 2HDY), 49 (42). This result shows that the structure of SCL is quite similar to that of human SCL, and more similar to those of group I cysteine desulfurases (IscS and NifS-like protein) than those of group II cysteine desulfurases (SufS and CsdB) (35,43) (Fig. 3B).…”
Section: Esi-ms Analysis Of Enzymeboundmentioning
confidence: 75%
“…E. coli contains iscS and two other paralogs, csdA and sufS (csdB). These enzymes can be placed into two groups, based on sequence of an active site loop that contains an essential cysteine and other criteria (13). By these criteria, E. coli IscS is a group I enzyme, whereas SufS and CSD are members of group II.…”
mentioning
confidence: 99%